Preparation and Properties of a Kind of Hydrophilic Polyimide Film with Quaternary Ammonium Salt Structure. Issue 1 (January 2021) - XueFang,; Su, Guiming; HaijianJiang,; MingyueChen,; XiaodongLiu,; MeihuiSong,; XiaochenZhang,
Abstract: We synthesized a polyamide acid by copolycondensation reaction using diphenyl ether tetraacid dianhydride (ODPA) as the dianhydride monomer, diaminodiphenyl ether (ODA) and N-methyl-2, 2-diaminodiethylamine (diethylamine) as the diamine monomer. Then the polymer with side-linked branch sulfonate structure was synthesized, and the structure of quaternary ammonium salt was added to the polyamide acid. A hydrophilic PI film was prepared by coating and thermal imidization process. The main influence factors in the formation process of hydrophilic PI film were discussed, then its hydrophilic properties and thermal properties were tested. The results show that diethylamine can react with lactone in the PI molecular chain in the DMAc system. The introduction of quaternary ammonium salt significantly improves the hydrophilic properties of the polyimide film surface, the water contact angle of the film dried at 130°C is 58.065°. Above 140°C, breakage and decomposition of the -N + SO3 − structure bond will occur, and the hydrophilic property will decrease.